Metal music and the re-imagining of masculinity, place, race and nation - Spracklen, Karl (Emerald studies in metal music and culture., 2020)
Metal is a form of popular music. Popular music is a form of leisure. In the modern age, popular music has become part of popular culture, a heavily contested collection of practices and industries that construct place, belonging and power. The arrival of Donald Trump in the White House has shown that angry white men still wield huge social and cultural power in this new century. The aim of this monograph is to explore metal music - might be seen as leisure spaces that resist the norms and values of the mainstream; but also how they might also serve to re-affirm and construct those norms and values. In particular, this book is interested in how forms of metal might work to re-imagine masculinity, race, nation and class in an intersectional way through the myth of warrior masculinity and blood and soil. This monograph explores the history of the myths, and the reaction by fans to the music. The focus is extended to bands that use the warrior-nation myth in places and countries beyond the global North, and in ways that challenge or subvert hegemony.